Analisis Deskriptif Kelengkapan Fasilitas Kandang Ayam sebagai Dasar Perbaikan Kandang - Alifa Permata Dewi (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
MUSA FARM is a farm raising ELBA and KUB native chickens in Parit Malintang, Padang Pariaman Regency. The completeness of chicken coop facilities plays an important role in supporting livestock health, operational smoothness, and farm productivity. This study aims to analyze the condition of the completeness of chicken coop facilities and to identify facilities that are not yet available or need improvement. The facilities analyzed include the environment, feeding troughs, ventilation, and other supporting equipment. The study employed a descriptive analysis method with data collection techniques through observation, interviews, and documentation. Data were analyzed descriptively to describe the actual condition of the facilities available in the chicken coop. The results of this study are expected to provide information regarding the level of completeness of coop facilities and to serve as a basis for formulating improvement recommendations to support chicken health, enhance operational efficiency, and optimize farm productivity.